(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
This paper aims to investigate the dependence and independence between the variables inferred in the bibliometric analysis of the literature on corporate social responsibility (CSR), business sustainability (BS), and integrated reporting (IR). In this paper, we undertook a bibliometric analysis with statistical analysis to fulfill the proposed goal, based on scientific papers from 1975 to 2021 indexed by ISI Web of Science and SCOPUS databases on the abovementioned topics. The results are the development of a model for mapping future research directions on IR, CSR, and BS issues using the clustering method. The bibliometric and statistical analysis can help researchers by providing clear guidelines for future studies, depending on the behaviour of research clusters on the IR topic. Previous studies didn’t attempt to analyze future research directions of IR from a bibliometric and statistical standpoint, which should be carefully tracked, because IR can offer support to companies by improving their communication with stakeholders.